Programming Elasticity in the Cloud. - Truong, Hong-Linh; Dustdar, Schahram (Computer (00189162), 2015)
As a virtualized environment, the cloud offers considerable flexibility. Maximizing its benefits requires incorporating elasticity as a "first-class" property throughout the cloud software development life cycle.